The Impact of Kitchen Gardening on the Social and Economic State of Rural Women: Bihar Sustainable Livelihood Development (BSLD) Project supported by Heifer International - Shukla, Karunesh; Kumar, Amit (Heifer International, 2023)
The abstract highlights the transformative power of kitchen gardening in empowering smallholder women farmers, promoting gender equality, and ensuring nutrition, food security, and health within Bihar’s Sustainable Livelihood Development (BSLD) project. Launched in 2020 by Heifer International, the project aims to provide sustainable livelihood opportunities for small and marginal holder farmers over the next five years. Kitchen gardening enables smallholder women farmers to take control of household food production, ensuring access to fresh and healthy food and contributing to improved food security. It also empowers women by promoting autonomy and decision-making power in shaping household food security. Through anecdotal findings and interactions with women smallholder farmers, it has been observed that kitchen gardening has a significant positive impact on their social and economic well-being. It provides them with a sense of empowerment, and improved decision-making power, fostering social cohesion within the community. The BSLD project also focuses on promoting a balanced diet through Panchranga Bhojan, an educational initiative that encourages smallholder women farmers to adopt diverse and nutritious diets for better overall health outcomes. Moreover, kitchen gardening plays a vital role in the economic stability of smallholder women farmers by reducing reliance on external markets, lowering expenses, and generating additional income through the sale of surplus produce in local markets. This economic stability enhances their financial well-being and contributes to broader food security efforts. In conclusion, kitchen gardening proves to be a powerful tool in empowering smallholder women farmers, promoting gender equality, improving nutrition, and more.